Affordances of cul-de-sac in urban neighborhoods as play spaces for middle childhood children - Othman, Sumaiyah (2010)
Cul-de-sac does not have to be defined as a dead-end or some refer it as a lost space. Even though it is heavily criticized by urban designers and other experts for encouraging car transport for even short distances, as more direct connections are cut off by the dead-end geometry which requires long travel distances even to physically nearby locations and can caused great difficulty with turning around for bus or in emergency situation. Sometimes, this informal space can have more utilitarian that often unnoticed by adults. This study is to investigate and identify the affordances and potential of culde- sac design in urban neighborhoods rather than just a defensible space in housing layout but as play spaces for middle childhood children in Malaysia. Data of the children behavioural responses were elicited using research design called observational study with paired data; comparing the differences of the children’s functioning in two cul-desacs. This study investigates the middle childhood children, on the utilization of cul-desac in their home or neighbouring area. Responses of eighty-two (n=82) children aged 6- 12 were gathered from two sources: children and parents using three methods –semistructured interviews, observation and survey questionnaire. The methods were conducted at cul-de-sac near their home and neighbouring cul-de-sac in two neighborhood in urban areas. The first area was at housing neighbourhood at Jalan Bakti, Taman Mutiara Rini, Johor that was characterized by its modern houses and has cul-desac at the end of its streets. Meanwhile the other site was at Taman Lagenda, Bukit Jelutong, Selangor. The data were analyzed using descriptive statistics and content analysis. This study suggests that it is not the aesthetic design of the cul-de-sac but caregiver’s permission and the affordances of sociality that encourage the children to play in the cul-de-sac. This study implies that children in Taman Lagenda, Bukit Jelutong, Selangor ventures more to be physically and socially interactive compared to children in Jalan Bakti, Taman Mutiara Rini, Johor where the monotonous properties in their cul-de-sacs afforded the children to be less active to play but socially active with their peers. This study will help to give different view how adults specially professionals can interpret and not be underestimated the cul-de-sac design in housing layout as children play spaces.